Angiosperm-Wide and Family-Level Analyses of AP2/ERF Genes Reveal Differential Retention and Sequence Divergence After Whole-Genome Duplication - Wang, Linbo; Ma, Hong; Lin, Juan (Frontiers in Plant Science, 2019)
Plants are immobile and often face stressful environmental conditions, prompting the evolution of genes regulating environmental responses. Such evolution is achieved largely through gene duplication and subsequent divergence. One of the most important gene families involved in regulating plant environmental responses and development is the AP2/ERF superfamily; however, the evolutionary history of these genes is unclear across angiosperms and in major angiosperm families adapted to various ecological niches. Specifically, the impact on gene copy number of whole genome duplication events occurring around the time of the origins of several plant families is unknown. Here, we present the first angiosperm-wide comparative study of AP2/ERF genes, identifying 75 Angiosperm OrthoGroups (AOGs), each derived from an ancestral angiosperm gene copy. Among these AOGs, 21 retain duplicates with increased copy number in many angiosperm lineages, while the remaining 54 AOGs tend to maintain low copy number. Further analyses of multiple species in the Brassicaceae family indicated that family-specific duplicates experienced differential selective pressures in coding regions, with some paralogs showing signs of positive selection. Further, cis regulatory elements also exhibit extensive divergence between duplicates in Arabidopsis. Moreover, comparison of expression levels suggested that AP2/ERF genes with frequently retained duplicates are enriched for broad expression patterns, offering increased opportunities for functional diversification via changes in expression patterns, and providing a mechanism for repeated duplicate retention in some AOGs. Our results represent the most comprehensive evolutionary history of the AP2/ERF gene family, and support the hypothesis that AP2/ERF genes with broader expression patterns are more likely to be retained as duplicates than those with narrower expression profiles, which could lead to a higher chance of duplicate gene subfunctionalization. The greater tendency of some AOGs to retain duplicates, allowing expression and functional divergence, may facilitate the evolution of complex signaling networks in response to new environmental conditions.